Vocal folds vibrations with a three-dimensional deformable model - Montagnoli, Arlindo Neto [UNESP]; Rubert, Jose Benaque; Guido, Rodrigo Capobianco; Pereira, Jose Carlos (Institute of Electrical and Electronics Engineers (IEEE), 2006)
In this work a computational method is presented to simulate the movements of vocal folds in three dimensions. The proposed model consists of a mesh free structure where each vertex is connected its neighbor through a group spring-damper. Forced oscillations were studied by time varying surface forces. The preliminary results using this model are similar with the literature and with the experimental stroboscopic observations of larynx. © 2006 IEEE.
Keywords: Computational methods; Technical presentations; Three dimensional; Deformable modeling; Forced oscillations; International symposium; Mesh free; surface forcing; Three dimensional (3D); Three dimensions; Time varying; vocal folds; Mesh generation